Public health and Bioethics: The work of the epidemiologist Mervyn Susser - Ασπραδάκη (Aikaterini Aspradaki), Αικατερίνη; Φιλαλήθης (Anastasios Philalithis), Αναστάσιος (Bioethica, 2017)
The multidisciplinary academic and practical field of public health is increasingly interesting for researchers in bioethics. The current paper, whose aim is to explore the origins of the enquiries of bioethics with respect to public health, focuses on the 1960’s and 1970’s, a period when modern bioethics developed, but also a period when important developments occurred in public health. At that time, the scientific field of epidemiology draws the attention of pioneers in public health and many would describe it as a period of historical transition, in the development and establishment of modern epidemiological methods. The paper draws on the work of the epidemiologist Mervyn Susser, one of the great personalities of epidemiology in the 20th Century, and an exponent of a type of epidemiology that is deeply rooted in public health. He was a fighter for social justice, who, in his long scientific career, strived to demonstrate the interdependency of social injustice and the health of populations and who combined anti-apartheid politics, clinical practice, sociology, epidemiology, the study of the scientific method and history. His work ranks him amongst the founders of scientific areas such as social epidemiology, life-course epidemiology, genetic epidemiology, the epidemiology of neuro-developmental disorders and global health. The work of Susser in the 1960’s and 1970’s and its relevance to bioethics is presented in three phases: The first refers to causality in epidemiology, the second to the history of responsibilities in public health and the third to issues of ethics in epidemiology. It is concluded that the relationship between public health and bioethics shows strong common interests that are established and expanded in the 1960’s and 1970’s by scientists such as the epidemiologist Mervyn Susser. In the 21st Century, this relationship provides the basis for the cooperation between ethics and a public health- based epidemiology, in order to achieve a bioethically committed global social justice.